Progress and Prospects of Bioelectrochemical Systems: Electron Transfer and Its Applications in the Microbial Metabolism - Zheng, Tianwen; Li, Jin; Ji, Yaliang; Zhang, Wenming; Fang, Yan; Xin, Fengxue; Dong, Weiliang; Wei, Ping; Ma, Jiangfeng; Jiang, Min (Frontiers in Bioengineering and Biotechnology, 2020)
Bioelectrochemical systems are revolutionary new bioengineering technologies which integrate microorganisms or enzymes with the electrochemical method to improve the reducing or oxidizing metabolism. Generally, the bioelectrochemical systems show the processes referring to electrical power generation or achieving the reducing reaction with a certain potential poised by means of electron transfer between the electron acceptor and electron donor. Researchers have focused on the selection and optimization of the electrode materials, design of electrochemical device, and screening of electrochemically active or inactive model microorganisms. Notably, all these means and studies are related to electron transfer: efflux and consumption. Thus, here we introduce the basic concepts of bioelectrochemical systems, and elaborate on the extracellular and intracellular electron transfer, and the hypothetical electron transfer mechanism. Also, intracellular energy generation and coenzyme metabolism along with electron transfer are analyzed. Finally, the applications of bioelectrochemical systems and the prospect of microbial electrochemical technologies are discussed.